Dopamine polymer derived isolated single-atom site metals/N-doped porous carbon for benzene oxidation. Issue 63 (6th July 2020) - Wu, Konglin; Zhan, Fei; Tu, Renyong; Cheong, Weng-Chon; Cheng, Yuansheng; Zheng, Lirong; Yan, Wensheng; Zhang, Qinghua; Chen, Zheng; Chen, Chen
Abstract : Isolated single-atom sites metals/nitrogen-doped porous carbon (ISAS M/NPC, M = Fe, Co, Ni) are prepared by a polymerization-pyrolysis-etching-activation strategy, which can be used as high efficiency and selectivity benzene oxidation catalysts. Abstract : Isolated single-atom site metals/nitrogen-doped porous carbon (ISAS M/NPC, M = Fe, Co, Ni) catalysts are successfully prepared by a top–down polymerization-pyrolysis-etching-activation (PPEA) strategy, which uses dopamine as the precursor. Due to the isolated single atom Fe active sites and porous structure, the ISAS Fe/NPC catalyst displays a high benzene conversion up to 42.6% and nearly 100% phenol selectivity.